2009
DOI: 10.1016/j.socscimed.2008.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Children's delayed development and behavior problems: Impact on mothers' perceived physical health across early childhood

Abstract: Mothers of children with developmental delays may experience poorer psychological well-being than other mothers; however, little research has examined how delayed development in children might predict mothers' perceived physical well-being. Children with delayed development manifest heightened behavior problems, which may negatively affect maternal well-being. We examined the associations between developmental delay and behavior problems at child age 3 and mothers' selfperceived physical health at child ages 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
79
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 52 publications
(64 reference statements)
6
79
1
2
Order By: Relevance
“…Prior research has suggested a transactional relationship between child behavior and parental stress and coping (Baker et al, 2003;Eisenhower, Baker, & Blacher, 2009). Mancini et al (2000) have shown that severity of impairment can influence the participation patterns of school-aged children.…”
Section: Managing Behavior When Accessing Community Eventsmentioning
confidence: 99%
“…Prior research has suggested a transactional relationship between child behavior and parental stress and coping (Baker et al, 2003;Eisenhower, Baker, & Blacher, 2009). Mancini et al (2000) have shown that severity of impairment can influence the participation patterns of school-aged children.…”
Section: Managing Behavior When Accessing Community Eventsmentioning
confidence: 99%
“…Parenting stress is considered an environmental risk factor (Neece, Green, & Baker, 2012) that increases parents' depression, couple conflicts, physical disease rates, intrafamily violence (see Eisenhower, Baker, & Blacher, 2009;Hasting, Daley, Burns, & Beck, 2006;Kersh, Hedvat, Hauser-Cram, & Warfield, 2006;Stith et al, 2009), and children's social-emotional and behavioral problems (Tharner et al, 2012). Parenting stress is also associated with insecure attachment in foster children (Gabler et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Transient physical impairments, such as motor delays or lowered ability to perform daily activities, may not be alarming if children can eventually catch up to their peers. A prolonged impairment, however, would place considerable burden on the patient and family (30).…”
mentioning
confidence: 99%